Structural analysis across length scales of the scorpion pincer cuticle - Kellersztein, Israel; Greenfeld, Israel; Wagner, H Daniel (Bioinspiration & biomimetics, 2021)
Biological structures such as bone, nacre and exoskeletons are organized hierarchically, with the degree of isotropy correlating with the length-scale. In these structures, the basic components are nanofibers or nanoplatelets, which are strong and stiff but anisotropic, whereas at the macrolevel, isotropy is preferred because the direction and magnitude of loads is unpredictable. The structural features and mechanisms, which drive the transition from anisotropy to isotropy across length scales, raise fundamental questions and are therefore the subject of the current study. Focusing on the tibia (fixed finger) of the scorpion pincer, bending tests of cuticle samples confirm the macroscale isotropy of the strength, stiffness, and toughness. Imaging analysis of the cuticle reveals an intricate multilayer laminated structure, with varying chitin-protein fiber orientations, arranged in eight hierarchical levels. We show that the cuticle flexural stiffness is increased by the existence of a thick intermediate layer, not seen before in the claws of crustaceans. Using laminate analysis to model the cuticle structure, we were able to correlate the nanostructure to the macro-mechanical properties, uncovering shear enhancing mechanisms at different length scales. These mechanisms, together with the hierarchical structure, are essential for achieving macro-scale isotropy. Interlaminar failure (ILF) analysis of the cuticle leads to an estimation of the protein matrix shear strength, previously not measured. A similar structural approach can be adopted to the design of future synthetic composites with balanced strength, stiffness, toughness, and isotropy.